Eliot in his time : essays on the occasion of the fiftieth anniversary of "The Wasteland" - Litz, A. Walton (Princeton legacy library., 1973)
The essays in this new collection, all by outstanding experts in the field of modern literature, provide a different and more complex sense of Eliot's place in literary history. The eight essays are: "The Waste Land Fifty Years After," by A. Walton Litz; "The Urban Apocalypse," by Hugh Kenner; "The First Waste Land:' by Richard Ellmann;" The Waste Land: Paris 1922," by Helen Gardner; "New Modes of Characterization in The Waste Land," by Robert Langbaum; "Precipitating Eliot," by Robert M. Adams; "Fear in the Way: The Design of Eliot's Drama," by Michael Goldman; and "Anglican Eliot," by Donald Davie. Originally published in 1973. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905